Search and equilibrium prices: Theory and evidence from retail diesel - Luís M. B. Cabral; Dominik Schober; Oliver Woll (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
We examine the relation between consumer search and equilibrium prices when collusion is endogenously determined. We develop a theoretical model and show that average price is a U-shaped function of the measure of searchers: prices are highest when there are no searchers (local monopoly power) or when there are many searchers (and sellers opt to collude). We test this prediction with diesel retail prices in Dortmund, Germany. We estimate a U-shaped relation with statistical precision and a exteuro.025/liter price variation due to the variation in the measure of searchers.
Keywords: L1; L4; L5; L9; 330; Collusion; Cartelization; Fuel Retailing; Search; Competitive Intensity